The Decentring of the Historical Subject in the Contemporary Imaginary of the Independence Process - Pizarro-Cortes, M (2011)
This paper offers an analysis of several contemporary forms of the historical subject s representation - essays, novels, poems, comics, documentaries, films and soap operas - all of which contribute to shaping a new collective imaginary of the independence process in Latin America. All of these representations have in common the decentring of the historical subject. This operation can be verified in at least three variations: (1) the decentring of the figure of the hero, (2) the emergence of alternative heroes (popular heroes and heroines), and (3) the visibilization of marginalized historical subjects because of their ethnic origin (Amerindians, Afro-American, mulattos and mestizos). © 2011 Copyright Taylor and Francis Group, LLC.